José de Alencar e as Visões de Brasil - Peloggio, Marcelo Almeida (2006)
This study aims to elaborate a dialogue between the aesthetical, political and philosofical ideas about the Brazil of José de Alencar and those ones which are linked to the most important currents of thoughts that, in Alencar s brief lifetime (1829-1877), were already in force or were still in development. It intend s equally to discuss some concepts that, in the last eighty years, were presented by the criticism concerning to his work, labored by brazilian as much as portuguese authors.